SURGICAL TREATMENT OF GASTROINTESTINAL BLEEDING IN PEPTIC ULCER PATIENTS: EMERGING CONCEPTS - A. I. Tchernookov; B. A. Naumov; V. S. Alexeev; E. S. Silchuk; F. G. Tolibov (Сеченовский вестник)
Approaches to determination of prognosis and management of patients with peptic ulcer disease, complicated with gastrointestinal bleeding